Сучасні методи керування брагоректифікаційними установками - Гриценко, Н. Г.; Ладанюк, А. П.; Луцька, Н. М.; Смітюх, Я. В.; Кириленко, Р. Г. (Енергетика і автоматика, 2017)
MODERN METHODS OF MANAGEMEN GROUT`S RECTIFICATIONS INSTALLATIONSN. Gricenko, A. Ladanyuk, N. Lutska, Y. Smityuh, R. KirilenkoNational University of Food Technologies Automation of domestic distilleries using single-stabilization system that are based on the standard control algorithms that do not satisfy the requirements of management under uncertainty do not provide decision making for management and optimization of the basic processes of technological complex distillery, did not allow for timely response on various technological situations arising from changes in key input and output parameters. This leads to wasteful power consumption and reduce the productivity of the company.Such systems do not solve the main problems of cost, quality and power consumption of alcohol production. That's why before automation systems for the production of rectified ethyl alcohol is an effective problem management process aimed at significantly reducing energy consumption while maintaining the quality of the finished product.By analyzing the characteristics of the facility and its operation features formed integrated approach to management, which is the synthesis optimization techniques, adaptation, compensation disturbances and delays, robust stabilization of innovative intelligent systems that are based on robust controllers, fuzzy logic and neural-fuzzy networks.To solve this problem created management information system (MIS), on top of which is a subsystem of decision support (DSS), which analyzes the actual situation, search for and making decisions based on existing databases (DB) knowledge base (KB ) and created for this class of object database models (DM).At the lower level of the system is placed object control (OC), consisting in this case of the subsystems of a single column grout`s (CG), grout`s department (GD) and boiler.The structure of the MIS is designed to improve the quality of operations, improve quality performance of the control system. Thus, the complex of decisions aimed at improving the quality of the finished product, to reduce energy intensity installation of this type and to reduce the percentage of waste in the alcohol industry.